Treatment with Botulinum Neurotoxin Improves Activities of Daily Living and Quality of Life in Patients with Upper Limb Tremor. (26th July 2019) - Kreisler, Alexandre; Bouchain, Benoîte; Defebvre, Luc; Krystkowiak, Pierre
Background: Botulinum neurotoxin's degree of effectiveness on upper limb tremor is subject to debate; although this treatment reduces the tremor's amplitude, a clear functional benefit has not been demonstrated. The objective of this study was to assess the effect of botulinum neurotoxin type A treatment on activities of daily living and quality of life in patients with upper limb tremor. Methods: We retrospectively examined the medical records of 50 consecutive patients treated with botulinum neurotoxin for upper limb tremor that was refractory to oral medication. One month after the injection, the patient was evaluated according to the Quality of Life in Essential Tremor Questionnaire, and the Essential Tremor Embarrassment Assessment. Results: Full data sets were available for 38 patients suffering variously from essential tremor ( n = 21), Holmes tremor secondary to a focal brain lesion (n = 8), idiopathic dystonic tremor (n = 4), primary writing tremor (n = 4), and Parkinson's disease (n = 1). The Quality of Life Essential Tremor Questionnaire and the Essential Tremor Embarrassment Assessment scores improved significantly (p < 0.001) in the study population as a whole, and in the essential tremor and Holmes tremor subgroups. Discussion: Botulinum neurotoxin treatment of patients with upper limb tremor is associated with improved quality of life and activities of daily living, irrespective of the tremor's etiology. Long-term treatment enables the physician to adjust the injection strategy to the patient's needs. Our study was limited by its retrospective design. The results must therefore be confirmed in a prospective, double-blind, placebo-controlled, randomized clinical trial.